(untitled) (Journal on Excellence in College Teaching, 2024)
The author explores concrete ways to help students learn more and have fun doing it while they support each other’s learning. The article specifically shows the relationships between cooperative learning and deep learning. Readers will become familiar with the tenets of cooperative learning and its power to enhance learning-even more so when it is carefully structured and sequenced to promote deep learning. Concrete examples also offer some practical applications.